The Role of Conveyancer in Resolving Disputes against the Deed - Ajeng Pusparini; Gunarto Gunarto (Sultan Agung Notary Law Review, 2021)
Dispute and land conflict is a form of problems that are complex and multi-dimensional. In such disputes often involve the Land Deed Official to account for the deed he made, the National Land Agency as a Facilitator in the handling of land disputes involving land deed. Research method used is empirical juridical, the specification of this research uses descriptive method of analysis, the method of data analysis used is using the method of literature research, based on research concluded so that conveyancer can apply the principle of prudence by conducting field checks, that in handling land disputes it takes good faith and each party must be cooperative in the course of mediation.